A review of visual perspective taking in autism spectrum disorder - Pearson, Amy; Ropar, Danielle; Hamilton, Antonia F. (Frontiers in Human Neuroscience, 2013)
Impairments in social cognition are a key symptom of Autism Spectrum Disorder. People with autism have great difficulty with understanding the beliefs and desires of other people. In recent years literature has begun to examine the link between impairments in social cognition and abilities which demand the use of spatial and social skills, such as visual perspective taking (VPT). Flavell (1977) defined two levels of perspective taking: VPT level 1 is the ability to understand that other people have a different line of sight to ourselves, whereas VPT level 2 is the understanding that two people viewing the same item from different points in space may see different things. So far, literature on whether either level of VPT is impaired or intact in autism is inconsistent. Here we review studies which have examined VPT levels 1 and 2 in people with autism with a focus on the methods that have been used to measure perspective taking. We conclude the review with an evaluation of the findings into VPT in autism and give recommendations for future research which may give a clearer insight into whether perspective taking is truly impaired in autism.